PENGAMPUNAN DOSA MENURUT AGAMA ISLAM DAN KRISTEN (SUATU KAJIAN PERBANDINGAN) - Marzuki, Bakri M. (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Islam and Christianity believe that Adam and Eve are their ancestors and that they have contravened Godâs prohibition to eat forbidden fruit (khuld). Islam believes that after Adam and Eve ate the forbidden fruit, they had asked for Godâs forgiveness so that God accepted their repents. However, Christianity does not believe that they have asked for Godâs forgiveness.Â Therefore, they are persistently sinful. Based on this, Christianity believes Adam and Eve to be sinful. Therefore, human beings are sinful because they have been born to sinful parents, Adam and Eve. Then the sin is called âoriginal sinâ because it was inherited by their sinful ancestors, Adam and Eve.